Fulminant granulomatosis with polyangiitis presenting with diffuse alveolar haemorrhage following COVID-19. Issue 6 (21st June 2021) - Lind, Eric; Jameson, Andrew; Kurban, Esaw
Abstract : A 40-year-old man developed granulomatosis with polyangiitis (GPA) following a mild case of COVID-19. Initially, he experienced mild migrating joint pain for 2 months prior to testing positive for SARS-CoV-2 but dramatically worsened following resolution of his infection. The pain continued to progress until he suddenly develope haemoptysis, prompting him to present to a local hospital. The diagnosis of diffuse alveolar haemorrhage secondary to GPA was confirmed with labs, imaging and histopathology. Precipitous deterioration of GPA with concurrent COVID-19 infection indicates a possible temporal relationship. Since the onset of the pandemic, SARS-CoV-2 has been anecdotally associated with the development of various connective tissue disorders. The overlapping clinical presentations and similar appearance on lung imaging present clinicians with a diagnostic challenge. This underscores the importance of having a high index of suspicion of autoimmune diagnoses in patients who present with new or worsening findings following a COVID-19 infection.